Evaluation of Islamic Banking product development process based on maqasid al-shari'ah : the case of sale-based and partnership-based home financing in Malaysia - Syahidawati binti Shahwan (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
The Islamic banking industry in Malaysia has made remarkable progress over the last three decades since the first bank was established in the country in 1983. Islamic banking has been able to cater for the wider needs of its customers, particularly Muslims, by providing various alternative products to the conventional system. One of these products is home financing, which constitutes a major share of its retail banking. Islamic home financing is largely offered through the Bay Bithaman Ajil (BBA) and Commodity Murabahah (Tawarruq), and to a lesser extent the Musharakah Mutanaqisah (MM), diminishing Partnership product. Over the years, Islamic banking has been criticised for its over reliance on the BBA product. Critics argue that BBA has been structured based on debt, replicating the conventional loan products, overburdens the customers in price, and hence does not conform to Maqasid al-Shariah. In contrast, they see MM as promising because it is just, equitable, and conforms to the Maqasid. Nevertheless, MM has also been criticised for failing to meet al-Maqasid. The cases of BBA and MM are typical of the trends in most Islamic banking products. When these products are developed and launched in the market, they are accredited for fulfilling Maqasid al-Shariah. With the span of time however, these products seem to fail this expectation. One therefore wonders whether it is true that these products fail to achieve Maqasid al-Shariah. If it is true, then at what stage in the process of developing these products does this failure occur? Most of the studies that discuss these products particularly BBA and MM in relation to their Maqasid have been scanty. There are a few empirical studies on the issues but most are explorative and descriptive. The present study fills this gap by investigating whether Islamic banking home financing products have failed to meet the Maqasid al-Shariah at the various stages of their development. The study has the Analytic Hierarchy Process (AHP) to prioritise and assess how BBA and Tawarruq (BBA&T) and MM achieve Maqasid al-Shariah at the stages of their product development. An extensive survey of the Maqasid and Islamic banking product development literature was conducted to identify the relevant criteria and sub criteria for constructing the AHP pair-wise comparison. The results show that MM conforms better to Maqasid at the various stages compared to BBA&T. Hence, MM home financing should be given priority when developing home financing products. Furthermore, at the first three stages of developing the two products, priority should be given to the preservation of the spiritual and mental wellness, followed by preserving social justice for both MM and BBA&T products. Moreover, in product commercialisation, institutional needs should be fulfilled first over customers' needs for both products. Future research can extend the present study to other Islamic banking products and services.